Defining the Flint Hills - Brian Obermeyer (Symphony in the Flint Hills, 2012)
The Flint Hills may be the best-loved natural area in Kansas. As the largest intact tallgrass prairie remaining in all of North America, it is also the state’s most ecologically significant landscape. The Flint Hills stretch north to south across east-central Kansas, and even extend on down into Oklahoma (where they are called the Osage Hills). The region’s width is relatively uniform, averaging perhaps 50 miles but reaching 75 miles at the widest.
Keywords: Flint Hills; North America; tallgrass; prairie; east-central Kansas; ecosystem; nature; grass; natural; Oklahoma; limestone; geologist; flint; Zebulon Pike; chert; homesteader; pioneer; settler; Osage Indian; Native American; glaciers; Quartzite; prairie-chicken; animals; plants; wildlife; pure; hillside